Optical goniometer for knee joint angle continuous monitoring - Ghassan Maan, Salim; Mohd Anwar, Zawawi (2021)
Knee joint is an important part of human body. People with poor knee condition generally have limited physical movement, rendering to mental stress and agony. Current technology to support the knee diagnosis and treatment procedures are limited to use of manual goniometer, x-ray and magnetic resonance imaging (MRI). X-ray and MRI technologies are useful to have some insight on the knee problem, but they are not applicable for continuous monitoring. One of the key methods used by physiotherapist to access knee health condition is by measuring knee joint angle during gait and identify the angular range for the knee movement of the patient in the frontal plane.